Red dragon fruit juice in reducing ros levels and insulin resistance In rats with type 2 diabetes mellitus model - Putri, Mahendri Deayu; Wiboworini, Budiyanti; Dirgahayu, Paramasari (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: The peel of red dragon fruit (Hylocereus polyrhizus) had been proven to have a total polyphenol content and total flavonoids 2 to 3 times more than its flesh. These components could reduce oxidative stress and maintain the function of pancreatic beta cells, which could affect blood sugar levels.Objectives: This study aimed to test the red dragon fruit juice using peel and flesh to reduce oxidative stress and insulin resistance in T2DM model rats.Materials and Methods: This study was a true experimental study with a randomized controlled trial, with a Matching Pretest Post-test Control Group Design. We used 21 white male rats (Rattus norvegicus) Wistar strain which was divided into three groups: (P1) negative control group (induced Streptozotocin + Nicotinamide induction), (P2) positive control group (given Streptozotocin + Nicotinamide and given Metformin HCl induction 0,9 mg/kg BW, and (P3) Red Dragon fruit group (induced Streptozotocin + Nicotinamide and given Red Dragon Fruit juice 3.6 ml / 200 g BW / day given for 14 days. The data were analyzed using a one-way ANOVA test, paired t-test, and Post Hoc.Results: After 14 days of intervention, the average HOMA-IR levels were as follows: negative control group (Mean=8.32; SD=0.26), positive group (Mean 4.89; SD=0.29), and the Red Dragon Fruit intervention group (Mean=4.65; SD=0.30). The average MDA levels were as follows: control group (Mean = 9.08; SD = 0.68), positive group (Mean=3.34;SD=0.22), and the red dragon fruit intervention group (Mean = 3.05; SD = 0.47). Both the Metformin group and the Red Dragon Fruit group had low HOMA-IR and MDA levels compared to the negative control group.Conclusions: When administered alone, red dragon fruit and metformin effectively reduced HOMA-IR and MDA levels in rats with type 2 DM. Red dragon fruit can be used as an alternative to metformin because of its effectiveness in reducing plasma HOMA-IR and MDA.